Problematika Perizinan Penyadapan Oleh KPK Pasca Revisi Undang-Undang Nomor 19 Tahun 2019 - Rachman, Andi Nur; Syarif, Mujar Ibnu (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2024)
The revision process of the Corruption Eradication Commission (KPK) Law resulted in structural changes with the formation of the KPK Supervisory Board. This change impacts the work procedures of KPK investigators, especially in conducting wiretapping of corruption suspects. This article analyzes the problematic issues of wiretapping permits by the KPK after the revision of Law Number 19 of 2019, which introduced a multi-layered bureaucracy. This study uses a normative legal method with statutory regulations. The results of the study indicate that the revision of the law requires the KPK to obtain permission from the Supervisory Board before conducting wiretapping, which has the potential to hinder the effectiveness and speed of investigations. However, after a judicial review was conducted at the Constitutional Court, it was decided that wiretapping could be carried out without permission from the Supervisory Board but must still be notified within a specific period. This decision is measured as a positive step in maintaining a balance between the effectiveness of corruption eradication and the accountability of the KPK institution.